Influência da infecção por Trypanosoma evansi sobre hormônios do sistema reprodutivo de ratos experimentalmente infectados - Faccio, Luciana (2012)
Infection by Trypanosoma evansi causes various pathological changes in animals, as well as reproductive problems whose pathogenesis is not fully known. Therefore, the objective of this study was to evaluate the serum concentrations of reproductive hormones, histopathology and biomarkers of oxidative stress in testicles of rats experimentally infected with T. evansi. Twenty four animals were divided in two groups with 12 animals each. Group A was formed by healthy Wistar rats (uninfected) and group B composed by animals infected with T. evansi. Both groups were divided into two subgroups (n=6) from which were collected serum and testicular fragments on day five and 15 post-infection. A significant reduction (P<0.01) in the levels of LH, FSH, testosterone and estradiol associated to the increase in cortisol levels was observed in serum of infected animals when compared to negative control. Also an increase in the concentrations of nitrite/nitrate (NOx), lipid peroxidation and protein oxidation was observed in the testicles. The histopathology showed testicular degeneration in the infected animals. Based on these results, we can conclude that infection with T. evansi may reduce the reproductive capacity of male and/or inducing infertility in rats, either directly or indirectly.